Deciphering seismic and normal‐force fluctuation signatures of debris flows: An experimental assessment of effects of flow composition and dynamics. Issue 11 (17th June 2021) - de Haas, Tjalling; Åberg, Amanda S.; Walter, Fabian; Zhang, Zhen
Abstract: Debris flows are gravity‐driven mass movements that are common natural hazards in mountain regions worldwide. Previous work has shown that measurements of ground vibrations are capable of detecting the timing, speed, and location of debris flows. A remaining question is to what extent additional flow properties, such as grain‐size distribution and flow depth can be inferred reliably from seismic data. Here, we experimentally explore the relation of seismic vibrations and normal‐force fluctuations with debris‐flow composition and dynamics. We use a 5.4 m long and 0.3 m wide channel inclined at 20°, equipped with a geophone plate and force plate. We show that seismic vibrations and normal‐force fluctuations induced by debris flows are strongly correlated, and that both are affected by debris‐flow composition. We find that the effects of the large‐particle distribution on seismic vibrations and normal‐force fluctuations are substantially more pronounced than the effects of water fraction, clay fraction, and flow volume, especially when normalized by flow depth. We further show that for flows with similar coarse‐particle distributions seismic vibrations and normal‐force fluctuations can be reasonably well related to flow depth, even if total flow volume, water fraction, and the size distribution of fines varies. Our experimental results shed light on how changes in large‐particle, clay, and water fractions affect the seismic and force‐fluctuation signatures of debris flows, and provide important guidelines for their interpretation. Abstract : This work experimentally explores the relation of seismic vibrations and normal‐force fluctuations with debris‐flow composition and dynamics, in a 5.4 m × 0.3 m flume channel inclined at 20°. The work shows that seismic vibrations and normal‐force fluctuations induced by debris flows are strongly correlated and that both are affected by debris‐flow composition. Effects of the large‐particle distribution are substantially more pronounced than the effects of water fraction, clay fraction, and flow volume, especially when normalized by flow depth.